Nutrition as an etiological factor causing diseases in endangered huemul deer - Fluck, Werner Thomas (2020)
Objectives: Distinct diseases prevent endangered huemul deer (Hippocamelus bisulcus) recovery. Fundamental etiological factors include nutriments, a mayor component of habitat quality. Undernutrition affects growth, skeletal development, osteopathology, reproduction and immunocompetence: this paper amplifies data corroborating micro-nutrient deficiencies among huemul. Results: In Argentina, 57% huemul cadavers exhibited osteopathology, with new cases reported here. Recently, 86% live huemul had osteopathology: cranial lesions involved antemortem tooth loss, reducing feeding efficiency and body condition, with starvation deaths. This population had tissues well deficient compared to other cervids, averaging 0.28 ppm selenium, 4.98 ppm copper, whereas for manganese 55% were deficient (2.52 ppm) and 45% adequate (42.79 ppm). Recently, lesions in one Chilean huemul were interpreted to stem from parapoxvirus. That population also has cases with cranial osteopathologies, high disease susceptibility (parapoxvirus, parasitism, foot lesions), crippled antlers, and low density, indicative of marginal habitat and primary etiological factors like undernutrition and immunosuppression. The reported atypical symptoms attributed to parapoxvirus may relate to probable diagnostic limitations, but does support presence of nutritional deficiencies. Patagonia has selenium deficient plants and livestock, including severe muscular dystrophy, and soil levels in extant huemul areas considered very deficient. Moreover, 73% of Chilean huemul were selenium deficient and 64% severely deficient with concomitant cranial osteopathology.